LAJU PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN BARONANG Siganus canalicalatus YANG DIBERI JENIS PAKAN DAN FREKUENSI YANG BERBEDA DI KERAMBA JARING APUNG - Naiboki Salampessy; irawati irawati (Jurnal Akuakultur Sungai dan Danau, 2021)
This research is about "Growth Rate and Survival Rate of Baronang Siganus canaliculatus Fish Given Different Types of Feed and Frequency in the Floating Net Cages. The research lasted as long as for 6 (six) months from May to October 2018.The design of this study used a factorial Completely Randomized Design (CRD) using 2 factors as treatment, namely: (1) 50% of the trash fish, 50% papaya leaves, and 25% trash fish & 75% papaya leaves. (2) the frequency of feeding once, the frequency of feeding 2 times and the frequency of feeding 3 times. This treatment is to see whether there is a significant difference between the treatment of growth rate and survival rate of baronang fish (Siganus canaliculatus) as the research sample. From the research data analyzed using ANOVA, it was found that the type of feed and the frequency of distribution had a significant effect on the growth rate. Based on statistics, the results of this study showed no significant effect between treatments on growth, survival and FCR. Feeding with a composition of 50% trash fish and 50% papaya leaves with a frequency of 3 times gave the highest growth rate, survival and FCR values for rabbit fish (Siganus canaliculatus) rearing for 120 days in Floating Net Cages